Penerapan Kecerdasan Buatan sebagai Media Pembelajaran Bahasa Arab di Era Society 5.0 - Aidah Novianti Putri; Moh. Abdul Kholiq Hasan (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2023)
This study aims to determine what is artificial intelligence (AI) and analyze several types of application of artificial intelligence as a learning medium in the era of society 5.0. Along with the increasing needs of the community for foreign languages, there is also an increase in the orientation to learn Arabic, which orientation begins to penetrate the realm of professionalism and economics. So that learning Arabic becomes one of the important agendas in the world of Education. However, learning Arabic in Indonesia still faces various obstacles and challenges in the era of society 5.0. This research is library research with qualitative descriptive approach. Data sources are books, journals, papers, and articles. Data collection techniques are done with documentation techniques. Data analysis used is content analysis. As for the results of the study, there are several applications of AI that are used as supporters or Arabic learning media in the era of society 5.0, including: Intelligent Tutoring System, Voice Assistant, Personalized Learning, Virtual Mentor, Smart Content, Automatic Assessment, and Game pendidikan . _